Atomistic studies of manipulation, growth and diffusion on FCC metal surfaces - Ghosh, Chandana (Kansas State University, 2003)
In this dissertation I present an extensive study of several issues related to manipulation, growth and diffusion of atoms and nanoclusters on fcc metal surfaces. One of the important aspects in understanding the effect of adatoms or clusters or even the effect of a tip is to examine the energy landscape of the surface in the presence of these objects. In our study of lateral manipulation using a tip, the use of the Grid method to obtain the energy landscape, has revealed useful information about the shift in the saddle point. Calculations on homogeneous as well as heterogeneous fcc(111) metal systems have been performed. Vertical manipulation on flat, stepped and kinked surfaces have given interesting results about the ease of manipulation on these surfaces. During growth, atoms at the edges of stepped surfaces experience an effect called the Kink Ehrlich Schwoebel Effect (KESE). Fluctuations that occur along the step edges play an important role in island decay for islands in the vicinity of a step edge, as observed in many experiments. Our standard Kinetic Monte Carlo (KMC) study on the vicinals of Cu(001) systems has shown that the KES barrier is in fact responsible for the ledge morphology that we see in our systems. To investigate cluster diffusion on fcc(111) systems which are more complex due to the occurrence of two types of step edge microfacets ((100) and (111)) in them, a KMC technique involving a unique pattern recognition scheme was developed to classify the environment of an atom. The energy barriers for different mechanisms were calculated extensively for Cu/Cu(111) as well as Ag/Ag(111) systems, using the NEB. The intriguing results obtained for these two-dimensional clusters, show magic cluster sizes having much lower diffusivity at 300 K as compared to the general clusters. The dependence of the diffusion coefficient on temperature as well as size of cluster has also been explored. Diffusion prefactors play an important role in the diffusion mechanisms. Most of the KMC studies assume a fixed prefactor. However, realistically this is not true. To get an understanding of the prefactors and their ratios for the important mechanisms, a study on the Ag/Ag(111) system shows that the ratio of the prefactors for step edge to terrace diffusion > 1, at low temperatures, which is in agreement with experimental observations. A molecular dynamics (MD) study was also performed to get an understanding of the initial evolution of certain clusters and the important mechanisms involved. All these investigations have given us a deep insight into several intriguing surface phenomena, observed in experiments and theoretical simulations.